Voxel-Based Analysis of Diffusion Tensor Imaging in Mild Traumatic Brain Injury in Adolescents - Chu, Z. (AJNR Am J Neuroradiol, 2010)
BACKGROUND AND PURPOSE: DTI of normal-appearing WM as evaluated by conventional MR imaging in mTBI has the potential to identify important regional abnormalities that relate to PCS. VBA was used to examine WM changes in acute mTBI. MATERIALS AND METHODS: WM was assessed between 1 and 6 days postinjury with voxel-based DTI analyses in 10 adolescent patients with mTBI and 10 age-matched control participants. In addition to the voxel-based group, analysis used to identify brain pathology across all patients with mTBI, 2 voxel-based linear regressions were performed. These analyses investigated the relation between 1) the ADC and PCS severity scores, and 2) ADC and scores on the BSI of emotional symptoms associated with mTBI. We hypothesized that frontotemporal WM changes would relate to symptoms associated with PCS and endorsed on the BSI. RESULTS: Patients with mTBI demonstrated significant reductions in ADC in several WM regions and in the left thalamus. As expected, no increases in ADC were found in any region of interest. All injury-affected regions showed decreased radial diffusivity, unchanged AD, and increased FA, which is consistent with axonal cytotoxic edema, reflective of acute injury. CONCLUSIONS: Whole-brain WM DTI measures can detect abnormalities in acute mTBI associated with PCS symptoms in adolescents.